Climate change's impact on key ecosystem services and the human well‐being they support in the US. Issue 9 (1st November 2013) - Nelson, Erik J; Kareiva, Peter; Ruckelshaus, Mary; Arkema, Katie; Geller, Gary; Girvetz, Evan; Goodrich, Dave; Matzek, Virginia; Pinsky, Malin; Reid, Walt; Saunders, Martin; Semmens, Darius; et al.
Abstract : Climate change alters the functions of ecological systems. As a result, the provision of ecosystem services and the well‐being of people that rely on these services are being modified. Climate models portend continued warming and more frequent extreme weather events across the US. Such weather‐related disturbances will place a premium on the ecosystem services that people rely on. We discuss some of the observed and anticipated impacts of climate change on ecosystem service provision and livelihoods in the US. We also highlight promising adaptive measures. The challenge will be choosing which adaptive strategies to implement, given limited resources and time. We suggest using dynamic balance sheets or accounts of natural capital and natural assets to prioritize and evaluate national and regional adaptation strategies that involve ecosystem services.